A new Eocene soldier beetle (Cantharidae) of the genus †Cacomorphocerus Schaufuss, 1892 from Baltic amber - Fanti, Fabrizio; Pankowski, Maximilian G. (Zootaxa, 2020)
Recent studies of extinct soldier beetles have generated an immense amount of new information. Scientists have described various new species of †Cacomorphocerus Schaufuss, 1892, confirming the remarkable diversification and evolution of this genus and the Cantharidae family during the Eocene. In the present work, we describe a new species from Baltic amber. Cacomorphocerus marki sp. nov., is the first species of Cacomorphocerus discovered with filiform 11-segmented antennae. Based on inclusions in Baltic and Rovno amber, it now appears certain that the genus Cacomorphocerus and the tribe Cacomorphocerini Fanti & Kupryjanowicz, 2018 evolved and subsequently went extinct in Europe during the Eocene. Known for more than 100 years from a single species, the genus is now known to be far more morphologically diversified thanks to these recent discoveries.